2019
DOI: 10.1016/j.celrep.2019.05.071
|View full text |Cite
|
Sign up to set email alerts
|

The Myb-MuvB Complex Is Required for YAP-Dependent Transcription of Mitotic Genes

Abstract: Highlights d YAP induces the expression and chromatin binding of the Myb-MuvB subunit B-MYB d YAP interacts with B-MYB-regulated promoters from distant enhancers d B-MYB is required for YAP-mediated expression of mitotic genes d The cooperation between YAP and B-MYB is critical for YAPmediated entry into mitosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 55 publications
(81 reference statements)
5
59
0
Order By: Relevance
“…YAP1-dependent cell lines and tumors showed enrichment in hallmarks related to cell cycle, such as the E2F targets, G2M checkpoint, MYC targets, and DNA repair pathways ( Figure 6C ). This is consistent with previous reports that have demonstrated that the transcription factors E2F and MYC are critical downstream regulators of YAP/TEAD-mediated activation of cell cycle genes ( Kapoor et al, 2014 ; Pattschull et al, 2019 ). While OSCC with high WWTR1 dependency signature score showed high expression of genes in several hallmarks related to immunity, such as the interferon responses, inflammatory responses and the complement pathway.…”
Section: Resultssupporting
confidence: 94%
“…YAP1-dependent cell lines and tumors showed enrichment in hallmarks related to cell cycle, such as the E2F targets, G2M checkpoint, MYC targets, and DNA repair pathways ( Figure 6C ). This is consistent with previous reports that have demonstrated that the transcription factors E2F and MYC are critical downstream regulators of YAP/TEAD-mediated activation of cell cycle genes ( Kapoor et al, 2014 ; Pattschull et al, 2019 ). While OSCC with high WWTR1 dependency signature score showed high expression of genes in several hallmarks related to immunity, such as the interferon responses, inflammatory responses and the complement pathway.…”
Section: Resultssupporting
confidence: 94%
“…Gene ontology analysis revealed that the MYC/β-catenin signature enriched-among othersfor Yap/Taz transcriptional targets (Supporting Table S3). Moreover, 59 of 125 genes (~45%) in our MYC/β-catenin signature (as opposed to ~14% of all active genes) scored as direct Yap targets by chromatin immunoprecipitation (28,29) (Biagioni et al, manuscript in preparation; Supporting Table S3). Finally, gene set enrichment analysis revealed that several Yap/Taz signatures were also enriched in the transcriptional profiles of either MYC/β-cat Ex3 or MYC-overexpressing livers (Supporting Fig.…”
Section: Concomitant Activation Of Myc and β-Catenin Induces A Pro-prmentioning
confidence: 99%
“…Given that Crim1 is characterized as a YAP1 target gene in a number of tumor cell lines 37 , 52 54 and is a critical regulator for lens development and lens epithelial integrity, 43 , 45 , 55 we examined Crim1 expression in the LEC of one-month-old Yap1 +/ − mice. The level of Crim1 mRNA in Yap1 +/ − LEC was reduced by 33% compared with WT LEC ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A number of genes have been identified as YAP1 targets, including Crim1. 37 41 CRIM1 is a type I transmembrane protein and has been studied in relation to cancer cell migration and invasion. 42 It is important for the maintenance of LEC polarity, proliferation, and adhesion interactions during lens development that most likely involves integrin signaling.…”
mentioning
confidence: 99%